Emerging Therapeutic Approaches for Amyotrophic Lateral Sclerosis (ALS) - Kushwaha, Neelottama; Kushwaha, Swatantra; Yadav, Priyank; Yadav, Nitika (Iranian Journal of Pharmaceutical Sciences, 2024)
Motor neuron disease (MND) is a collection of degenerative neurological disorders that impact the motor neurons responsible for controlling involuntary muscular movements. Amyotrophic lateral sclerosis (ALS) is the predominant variant, affecting both the upper and lower motor neurons in the brain and spinal cord. As the disease progresses, these neurons deteriorate, leading to muscle weakness, wasting, and inability to regulate voluntary motions. ALS can impair speech, swallowing, and breathing, causing significant impairment over time. Additional types of motor neuron disease (MND) encompass primary lateral sclerosis (PLS), progressive muscular atrophy (PMA), and progressive bulbar palsy (PBP). These types exhibit variations in the location and severity of motor neuron involvement, but they all share the progressive degeneration of motor neurons. Treatment may involve medication, physical therapy, assistive equipment, and supportive care to manage symptoms and consequences over time. This review's primary aim is crucial for gaining a deeper understanding of the disease's fundamental causes and creating innovative therapies or interventions to enhance the outlook and quality of life for individuals suffering from MND.